Identifikasi Hama Dan Penyakit Serta Pengendalian Pada Tanaman Cabai (Capsicum Annuum L.) Di Kelompok Tani Sinar Bahagia Desa Nitakloang Kabupaten Sikka - Kleruk, Yoseva Albertha; Beja, Hendrikus Darwin; Wahyuni, Yuyun (PUCUK : Jurnal Ilmu Tanaman, 2024)
Nita Kloang Village is one of the villages in Nita District, Sikka Regency, East Nusa Tenggara Province, with the majority of the population working as farmers. The leading commodity in this village is horticulture. The Sinar Bahagia Farmers Group is one of the farmer groups involved in chilli cultivation, including seeding and product processing. The Sinar Bahagia Farmers Group needs to pay attention to pests and diseases in chilli plants. The Independent Campus Competition Program (PKKM)-Village Development will take place in August-December 2024 in Nita Kloang Village, Nita District. The activity took place at the Sinar Bahagia Farmers Group. The methods used in this research are descriptive and primary methods. Descriptive data was collected through ongoing problems obtained directly at the research location. Primary data was obtained directly by the author. The procedures for identifying pests and diseases in chilli plants include determining observation blocks, identifying pests and diseases, analysing the level of attack, and knowing control.